Inter-City Spillover and Intra-City Agglomeration Effects among Local Labour Markets in China - Xiaodong Gong; Jiti Gao; Xuan Liang (Institute of Labor Economics (IZA), 2019)
We examine how city size affect wage levels of cities (agglomeration externality) and how it influence surrounding cities (spill-over effect) in China for the period between 1995 and 2009. Using spatial fixed-effect panel data models and allowing for endogenous and exogenous spatial dependence, we find strong positive city size effect on real wage levels, which confirms the existence of agglomeration economy within cities. We also find significant differences in both the direct and indirect effect of factors such as FDI between more and less population dense areas.
Keywords: C23; R12; R23; 330; agglomeration economy; spill-over; spatial econometrics; fixed-effects